2001
DOI: 10.1074/jbc.m101502200
|View full text |Cite
|
Sign up to set email alerts
|

Actin Cytoskeletal Association of Cytohesin-1 Is Regulated by Specific Phosphorylation of Its Carboxyl-terminal Polybasic Domain

Abstract: Cell adhesion mediated by integrin receptors is controlled by intracellular signal transduction cascades. Cytohesin-1 is an integrin-binding protein and guanine nucleotide exchange factor that activates binding of the leukocyte integrin leukocyte function antigen-1 to its ligand, intercellular adhesion molecule 1. Cytohesin-1 bears a carboxyl-terminal pleckstrin homology domain that aids in reversible membrane recruitment and functional regulation of the protein. Although phosphoinositide-dependent membrane at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…We found several lines of evidence to support a role for cytohesin-1 in CR3-dependent phagocytosis of BCG: 1) the uptake of serum-but not LBP-opsonized BCG was significantly attenuated in THP-1wt cells with knockdown cytohesin-1, 2) intracellular staining showed a CD14-and PI3K-dependent colocalization of cytohesin-1 with CR3 in LAM-stimulated cells, and 3) pull-down experiments detected the physical association between cytohesin-1 and either PtdIns-3,4,5-P 3 and CR3 in LAM-stimulated cells. This role for cytohesin-1 is also consistent with the observation that activated cytohesin-1 is able to tightly associate with the actin cytoskeleton (14).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We found several lines of evidence to support a role for cytohesin-1 in CR3-dependent phagocytosis of BCG: 1) the uptake of serum-but not LBP-opsonized BCG was significantly attenuated in THP-1wt cells with knockdown cytohesin-1, 2) intracellular staining showed a CD14-and PI3K-dependent colocalization of cytohesin-1 with CR3 in LAM-stimulated cells, and 3) pull-down experiments detected the physical association between cytohesin-1 and either PtdIns-3,4,5-P 3 and CR3 in LAM-stimulated cells. This role for cytohesin-1 is also consistent with the observation that activated cytohesin-1 is able to tightly associate with the actin cytoskeleton (14).…”
Section: Discussionsupporting
confidence: 75%
“…Pioneering studies by Kolanus et al (12) led to the discovery of an adaptor protein cytohesin-1, which interacts with the cytoplasmic tail of CD18 leading to changes in the functional properties of ␤ 2 integrins. Cytohesin-1 contains a pleckstrin homology domain that binds the PI3K metabolite, phosphatidylinositol 3,4,5-trisphosphate (PtdIns-3,4,5-P 3 ), leading to changes in properties of the protein (13,14). These findings have suggested a role for PI3K in regulating the activity of ␤ 2 integrins (15,16), which possibly includes CR3.…”
mentioning
confidence: 88%
“…The molecular mechanism by which cytohesin-1 regulates granule secretion remains to be studied, but a potential explanation may be provided by inhibition of the production of fusogenic lipids, such as PLD-derived PA (77) and/or the remodeling of the actin cytoskeleton (61). Indeed, the actin cytoskeleton regulates the secretion of several PMN granules (78), and a direct association of cytohesin-1 with the actin cytoskeleton has already been reported (54).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of cytohesin-1 and ARNO diglycine constructs to membranes requires the PH domain and is regulated by the C-terminal polybasic region (50,(52)(53)(54). We previously reported that cytohesin-1 triglycine is the major splice variant expressed in differentiated HL60 cells and that fMLF-induced translocation of cytohesin-1 to membranes, but not that of ARNO, was insensitive to inhibition by inhibitors of PI3K (10).…”
Section: Discussionmentioning
confidence: 99%
“…PH domains of cytohesins bind the lipid second messengers phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ) or phosphatidylinositol bisphosphate in vitro. The cytohesins seem to be involved in ARF6-mediated membrane trafficking and cytoskeletal reorganization Dierks et al, 2001;Santy and Casanova, 2001;Moss and Vaughan, 2002). In cells stimulated with an appropriate agonist, cytohesins can translocate from cytosol to plasma membrane to activate ARF6 in a phosphoinositide 3-kinase (PI3K)-dependent manner that requires both the PH and Sec7 domains of the cytohesin (Hemmings, 1997;Nagel et al, 1998b;Venkateswarlu et al, 1998;Venkateswarlu et al, 1999;Cullen and Chardin, 2000;Venkateswarlu, 2003).…”
mentioning
confidence: 99%